Orthodontic treatment needs according to the dental aesthetic index in 12-year-old adolescents, Chile - Pérez, María Antonieta; Neira, Álvaro; Alfaro, Javier; Aguilera, Juan; Alvear, Patricia; Fierro-Monti, Claudia (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: the objective of this study was to evaluate the needs for orthodontic treatment in 12-year-old adolescents from the towns of Ayacara, Cabrero, Coronel, and Niebla, Chile, according to the Dental Aesthetic Index (DAI). Methods: this was a descriptive, observational, cross-sectional, and non-probabilistic study. The DAI was applied on 129 12-year-old students from the rural towns of Ayacara, Cabrero, Coronel and Niebla in Chile. The sample was obtained by availability. Information was gathered through standardized clinical examinations carried out by previously calibrated researchers, following the WHO recommendations for this type of studies. The DAI criteria were descriptively analyzed, and statistical significance between males and females was considered. Results: out of the 129 patients, 65 (50.4%) were males and 64 (49.6%) females. 35.7% of the examined kids obtained DAI scores ≤ 25, which indicates normal occlusion to minimum malocclusion and means that treatment is unnecessary or slightly needed, 27.1% obtained scores between 26 and 30, which indicates evident malocclusion and optional treatment, 20.9% obtained a score ≥ 36, indicating very severe or handicapping malocclusion and mandatory treatment. Significant differences between males and females (P < 0,05) were observed in terms of missing anterior teeth only. Conclusions: there is a high need for orthodontic treatment in the adolescent population aged 12 years, as 64.3% of the sample presented definite malocclusion.